Epidemiology and audiologic characteristics of neonatal hearing loss: A cross-sectional study - Maojie Liu; Qiuying Xie; Xi He; Qiuya Jiang; Dan Lai (PLoS ONE, 2025)
Objective To explore the epidemiology and audiologic characteristics of neonatal hearing loss in neonates in southwestern China during 2020–2023. Methods This cross-sectional study involved all neonates born in Luzhou (China) during 2020–2023. Neonates with hearing loss (HL) were identified through initial hearing screening, rescreening, and diagnostic hearing test, and risk factors were determined using a questionnaire. Results From 2020 to 2023, there were a total of 109,562 neonates in Luzhou. Among them, 286 (465 ears) newborns were diagnosed with HL, with an incidence of 2.61 per thousand (2.61‰) (2020: 2.06‰, 2021: 2.89‰, 2022: 2.68 ‰, 2023: 3.00‰), and the difference in incidence between years was not statistically significant (P = 0.104). Among the affected ears, 234 (1.07‰) had mild HL, 130 (0.59‰) had moderate HL, 30 (0.14‰) had severe HL, and 71 (0.32‰) had profound HL. Additionally, 104 (0.95‰) children had unilateral hearing loss (UHL), while 182 (1.66‰) children had bilateral hearing loss (BHL), the incidence of UHL and BHL did not significantly differ across years (P = 0.33). There were 171 male children (2.99‰) and 115 female children (2.19‰) who were diagnosed with HL, and no significant difference was found in incidence between sexes (P = 0.10). The cause of HL remained unknown in 94 (32.87%) children, while 192 (67.13%) children had identifiable risk factors, including neonatal jaundice (93 cases), neonatal ward history (90 cases), pregnancy history (85 cases), and a family history of HL (24 cases). Of these, 113 (39.51%) children had multiple risk factors, while 79 (27.62%) children had only one identified risk factor. Conclusion During 2020–2023, the incidence of neonatal hearing loss is 2.61‰, which is not significantly increase, and no significant abnormal factors were identified.